The dark one eaudiobook - St. Crowe, Nikki (Vicious Lost Boys, 2022)
#1 BESTSELLER IN THE ENTIRE KINDLE STORE #9 ON AMAZON CHARTS I spent most of my life feeling dead inside  —  until I met Peter Pan and the Lost Boys. It wasn't until Pan and Neverland that I finally felt alive. But things are not all full of magic and sunlight on the island. There's something darker and more sinister haunting the forest. And worse, the fae queen and Captain Hook are ready to fight for control of Neverland and they will stop at nothing to get what they want. War is brewing—can the Never King get his shadow back and assume his rightful throne? And if he does, where will I fit? Or will all of Neverland be in jeopardy right along with my dark, twisted heart? NOTE: The Dark One is book two in the Vicious Lost Boys series. It is a dark reimagining of Peter and Wendy. If you like your enemies to lovers romance with hot, ruthless, morally gray love interests, you'll enjoy The Dark One. You can expect an island with darkness and secrets and no true hero in sight, with a found family atmosphere, and 'touch her and I'll unalive you' vibes. The Dark One ends on a cliffhanger. Please check the author's website for CWs.